Early management of capillary haemangioma to prevent stimulus-deprivation amblyopia - Ojha, Hare Ram; Verma, Neha (Nepalese Journal of Ophthalmology, 2022)
Introduction: Infantile capillary haemangiomas (IHs) are common, benign tumours that are self -limiting and generally found in the head and neck region.Case: We present a case of a three month old female baby who presented with a left upper eyelid capillary haemangioma because of which she could not lift the upper lid subjecting her to a high risk of stimulus- deprivation amblyopia.  Treatment was provided in the form of an intralesional Triamcinolone acetate injection (40 mg/ml) under general anaesthesia, along with oral Propranolol (1 mg/kg body in 2 divided doses for the first two days, followed by 2 mg/kg  in 2 divided doses for ten days (continued upto four months) and topical Timolol (0.5%) lid massage twice a day upto a period of six months.Observation: No adverse effects were reported and a marked reduction in size of the tumor was observed thereby providing an immediate relief to the child.Conclusion: Hence a combination therapy using intralesional steroids, along with oral propranolol and topical timolol over the lesion has proven to be very effective in providing early response.